Spray drying of shark liver oil pool: Effects on physical-chemical properties and antioxidant capacity - Caridad M. García (Journal of Pharmacy & Pharmacognosy Research, 2018)
Context: Spray-drying is a technique used to produce encapsulated products, thus improving the stability of components as well as their organoleptic characteristics.